Physiological Recovery from Stress is Associated with Spiritual Recovery: Findings from Awakened Awareness, a College-Based Spiritual-Mind-Body Intervention - Micheline R. Anderson; Suza C. Scalora; Abigail Crete; Elisabeth J. Mistur; Lisa Miller (Mary Ann Liebert, 2023)
Objective: Despite evidence of spirituality's protective benefits against psychological and physiological sequelae of stress, research has yet to provide empirical support for biological mechanisms of spiritually integrated interventions, thus limiting implementation in evidence-based Integrative Medicine approaches to illness. This study aims to provide evidence of physiological improvements in stress reactivity and recovery across the delivery of a spiritual?mind?body (SMB) intervention. Methods: This study examines heart rate variability (HRV) and self-report data collected before and after the delivery of a targeted preventive 8-week SMB wellness intervention (Awakened Awareness for Adolescents [AA-A]) to a nonclinically referred sample of emerging-adult undergraduates of a highly rigorous urban university. Participants (N?=?68; mean age?=?19) completed HRV collection across 5-min rest, stress, and recovery phases before and after delivering AA-A. Participants also completed a battery of validated self-report wellness and mental health measures, including the Patient Health Questionnaire (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), PTSD Civilian Checklist (PCL-C), Spiritual Transformation Scale (STS), and the Difficulties in Emotion Regulation Scale (DERS). Results: Significant improvements in high-frequency HRV, low-frequency HRV, and the high-low-frequency ratio were observed across recovery periods. Post-intervention recovery HRV was associated with changes in PTSD symptoms, spiritual decline, and emotion regulation. Significant regression models supported associations between improvements in postgroup HRV and improvements in emotion regulation and spiritual decline. Conclusions: These findings suggest that AA-A may support a spiritual and psychological recovery process that promotes psychophysiological resilience from stress in emerging adult college students. Assessing spiritual functioning and applying spiritually integrated interventions may support healing across spiritual, psychological, and physical domains. This line of inquiry warrants further investigation to fully understand the role of spiritual and psychological recovery in physiological resilience and recovery from stress.